THE ETHICAL PERCEPTION OF ACCOUNTING STUDENT: REVIEW OF GENDER, RELIGIOSITY AND THE LOVE OF MONEY - Julianto, Sahril; Kamayanti, Ari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This research aims to analyze whether there is a relationship between the level of religiosity, and the love of money on ethical perceptions of the accounting student. It also aims to find out if there are differences in the level of religiosity, the love of money and the ethical perception of accounting students based on gender. The discovery of the religiosity indicators is taken from the empirical studies with a qualitative approach on boarding schools Darul Muttaqin. The sample in this study is taken by using the data collection method called the purposive sampling. The number of samples that are used as many as 80 respondents. The Data obtained were analyzed using PLS (Partial Least Square) analysis technique via SmartPLS software. The results of this research show that there is a relationship between the level of religiosity and the love of money on accounting students with their ethical perception. The higher degree of religiosity of the students will be increasing the higher levels of perception of their ethical perception. The higher of the student’s love of money, then the lower level of their ethical perception will be. So does gender significantly influence the levels of religiosity, the love of money and the level of ethical perception of the accounting student. Key words: gender, religiosity, love of money, ethical perception and P